5問 引き算 分数引き算 数学・算数の教材公開ページ

20 

Loading....

Loading....

Loading....

Loading....

Loading....

全文

(1)

(1) 14

1

6 = (2)

5 3 −

5 6 =

(3) 74

5

6 = (4)

5 6 −

1 3 =

(5) 52

1 3 =

(2)

(1) 14

1 6 =

1

12

(2)

5 3 −

5 6 =

5

6

(3) 74

5 6 =

11

12

(4)

5 6 −

1 3 =

1

2

(5) 52

1 3 =

13

6

(3)

(1) 52

7

4 = (2)

1 2 −

1 4 =

(3) 23

1

2 = (4)

5 4 −

1 6 =

(5) 52

1 3 =

(4)

(1) 52

7 4 =

3

4

(2)

1 2 −

1 4 =

1

4

(3) 23

1 2 =

1

6

(4)

5 4 −

1 6 =

13

12

(5) 52

1 3 =

13

6

(5)

(1) 74

1

2 = (2)

1 2 −

1 5 =

(3) 53

5

6 = (4)

3 2 −

5 6 =

(5) 74

5 6 =

(6)

(1) 74

1 2 =

5

4

(2)

1 2 −

1 5 =

3

10

(3) 53

5 6 =

5

6

(4)

3 2 −

5 6 =

2

3

(5) 74

5 6 =

11

12

(7)

(1) 53

1

6 = (2)

4 3 −

5 6 =

(3) 43

1

6 = (4)

7 4 −

5 6 =

(5) 43

2 5 =

(8)

(1) 53

1 6 =

3

2

(2)

4 3 −

5 6 =

1

2

(3) 43

1 6 =

7

6

(4)

7 4 −

5 6 =

11

12

(5) 43

2 5 =

14

15

(9)

(1) 12

1

4 = (2)

2 3 −

1 6 =

(3) 32

1

4 = (4)

4 3 −

1 6 =

(5) 12

2 5 =

(10)

(1) 12

1 4 =

1

4

(2)

2 3 −

1 6 =

1

2

(3) 32

1 4 =

5

4

(4)

4 3 −

1 6 =

7

6

(5) 12

2 5 =

1

10

(11)

(1) 23

1

6 = (2)

5 3 −

1 2 =

(3) 52

3

4 = (4)

5 6 −

1 2 =

(5) 43

1 5 =

(12)

(1) 23

1 6 =

1

2

(2)

5 3 −

1 2 =

7

6

(3) 52

3 4 =

7

4

(4)

5 6 −

1 2 =

1

3

(5) 43

1 5 =

17

15

(13)

(1) 53

1

6 = (2)

5 4 −

5 6 =

(3) 52

1

5 = (4)

5 6 −

1 2 =

(5) 52

5 6 =

(14)

(1) 53

1 6 =

3

2

(2)

5 4 −

5 6 =

5

12

(3) 52

1 5 =

23

10

(4)

5 6 −

1 2 =

1

3

(5) 52

5 6 =

5

3

(15)

(1) 74

3

2 = (2)

3 2 −

2 5 =

(3) 45

1

2 = (4)

3 2 −

1 5 =

(5) 74

5 6 =

(16)

(1) 74

3 2 =

1

4

(2)

3 2 −

2 5 =

11

10

(3) 45

1 2 =

3

10

(4)

3 2 −

1 5 =

13

10

(5) 74

5 6 =

11

12

(17)

(1) 53

1

6 = (2)

3 2 −

3 4 =

(3) 53

5

6 = (4)

5 2 −

3 4 =

(5) 32

2 5 =

(18)

(1) 53

1 6 =

3

2

(2)

3 2 −

3 4 =

3

4

(3) 53

5 6 =

5

6

(4)

5 2 −

3 4 =

7

4

(5) 32

2 5 =

11

10

(19)

(1) 53

5

6 = (2)

5 3 −

1 6 =

(3) 45

1

3 = (4)

5 2 −

2 5 =

(5) 43

5 6 =

(20)

(1) 53

5 6 =

5

6

(2)

5 3 −

1 6 =

3

2

(3) 45

1 3 =

7

15

(4)

5 2 −

2 5 =

21

10

(5) 43

5 6 =

1

2

Updating...

参照

Updating...

関連した話題 :